The foundation of science and technology in view of Muhammad Abduh - Amir, Ahmad N.; Shuriye, Abdi Omar; Ismail, Ahmad Faris (Leena and Luna International,Oyama, Japan, 2012)

(untitled)
This paper highlighted the prominence of Muhammad ‘Abduh in science and technology and his contributions in developing scientific methodologies and principles. It discovered his ideas on science, technology, reason, revelation and rationality. It is important to note that Abduhu’s intention was to espouse universal framework of Islamic science. His scientific ideas were clearly presented in his works such as TafsirJuz ‘Amma, (Commentaries of Juz ‘Ammah) Tafsir al-Manar (Al-Manar Commentaries) and his masterpieces Al-Islam wa al-Nasraniyahma‘a al-Ilmwa al-Madaniyyah (Islam and Christianity in Relation to Science and Civilization) and Risalat al-Tawhid (The Theology of Unity). This worldview was projected fundamentally and centered on his effort to harmonize reason and revelation and finding new ground for Islamic science to be revived and revitalized. Many argue that his contributions to Islamic science were monumental in recognizing the dynamic interaction of revelation and reason and bringing progressive and rational understanding of the scripture which successfully accommodated the power of intellect and reason in modern times